Atypical Fibroxanthoma: An unexpected cause of hemoptysis - Mantzouranis, Konstantinos; Georgakopoulou, Vasiliki Epameinondas; Chlapoutakis, Serafeim; Melemeni, Despoina; Damaskos, Christos; Garmpis, Nikolaos; Sklapani, Pagona; Trakas, Nikolaos; Tsiafaki, Xanthi (Acta medica Lituanica, 2021)
Atypical fibroxanthoma is an infrequent, low-grade superficial cutaneous neoplasm, usually presenting as a nodule or plaque of red color. It is considered as a superficial variant of pleomorphic dermal sarcoma. Although atypical fibroxanthoma has similar histologic features to pleomorphic dermal sarcoma, it has less aggressive behavior. Atypical fibroxanthoma usually occurs on sun-exposed regions of the head and neck of elderly patients. Ultraviolet light, specific genetic mutations and administration of immunosuppressive agents to transplant recipients have been associated with the pathogenesis of the tumor. The prognosis is typically excellent when treated with complete excision of the primary lesion. This report describes the rare case of a 84-year-old man with hemoptysis due to metastatic cutaneous atypical fibroxanthoma.